Effectiveness of Online PAI Learning During the Covid 19 Pandemic at MAUWH Tambakberas Jombang - M Wafiyul Ahdi; Muhammad Ubaidillah (SCHOOLAR: Social and Literature Study in Education, 2022)
Education has an important role in building the Nation of Indonesia, one of which is in the learning process. Learning is said to be successful if the learning process runs effectively in accordance with the learning plan and objectives. In Indonesia, especially in MAUWH Tambakberas Jombang there was a change in the learning process that was initially face-to-face in school to Be Online ( Remote) because of the Covid 19 pandemic, therefore, this study aims to: 1.) Knowing the learning process pai online at MAUWH. 2.) Know the effectiveness of pai learning online at MAUWH. 3.) Know the advantages and disadvantages during the pai learning process online at MAUWH. In this case the researchers took the title " Effectiveness of Online PAI Learning During the Covid 19 Pandemic at MAUWH Tambakberas Jombang. This study uses descriptive qualitative methods based on the philosophy of postpositivism. The data collection used is obsrvasi, interview and documentation. Data source sampling is done purposively and snowbaal sampling. The results of this study can add new insights and can be used as a reference for further research. In this study, trianggulasi data collection techniques were conducted in 2021. The results of this study showed that the effectiveness of PAI online learning during the covid 19 pandemic at MAUWH Tambakberas Jombang did not work effectively due to the lack of interaction and reciprocal relationships between teachers and students as well as many obstacles in the online learning process such as the lack of discipline of students in following the learning process and the lack of smooth signal in remote areas to access the internet network.